Cinderella - Southgate, vera (London : Lady bird Ltd)
A wealthy widower has a beautiful young daughter, a girl of unparalleled kindness and sweet temper. The gentleman marries a proud and haughty woman as his second wife. She has two daughters, who are equally vain and selfish. The girl is forced to be a servant of the house by her stepmother, where she is made to work day and night doing menial chores. She often arises covered in ashes, giving rise to the mocking nickname (3z(BCinderella(3y (Bby her stepsisters. Cinderella bears the abuse patiently and does not tell her father. One day, the prince invites all the people in the land to a royal ball. The two stepsisters gleefully plan their wardrobes for the ball and taunt Cinderella by telling her that maids aren$1 (Bt invited to the ball. As the two stepsisters and the stepmother depart to the ball, Cinderella cries in despair. Her Fairy godmother magically appears and immediately begins to transform Cinderella from house servant to the young lady she was by birth, all in the effort to get Cinderella to the ball. She turns a pumpkin into a golden carriage, mice into horses, a rat into a coachman, and lizards into footmen. She then turns Cinderella$1 (Bs rags into a beautiful jewelled gown, complete with a delicate pair of glass slippers. The Fairy Godmother tells her to enjoy the ball but warns her that she must return before midnight when the spells will be broken. Everyone at the ball is mesmerized by Cinderella$1 (Bs beauty At the ball, the entire court is entranced by Cinderella, especially the Prince. At this first ball, Cinderella remembers to leave before midnight. Back home, Cinderella graciously thanks her Fairy Godmother. She then innocently greets the two stepsisters, who had not recognized her earlier, and talks of nothing but the beautiful girl at the ball. Another ball is held the next evening, and Cinderella again attends with her Fairy Godmother$1 (Bs help. The prince has become even more infatuated with the mysterious woman at the ball, and Cinderella in turn becomes so enchanted by him she loses track of time and leaves only at the final stroke of midnight, losing one of her glass slippers on the steps of the palace in her haste. The Prince chases her, but outside the palace, the guards see only a simple country girl leave. The prince pockets the slipper and vows to find and marry the girl to whom it belongs. Meanwhile, Cinderella keeps the other slipper, which does not disappear when the spell is broken. The Prince finds his princess The prince goes in search of the beautiful girl that he fell in love with and tries the slipper on all the women in the kingdom. When the Prince arrives at Cinderella$1 (Bs home, the two stepsisters try in vain to win him over. Cinderella asks if she may try, but the two stepsisters taunt her. Naturally, the slipper fits perfectly, and Cinderella produces the other slipper for good measure. Cinderella$1 (Bs stepfamily pleads for forgiveness, and Cinderella agrees. Cinderella had hoped her step-family would love her always. Cinderella marries the prince and forgives her two stepsisters, then marries them off to two wealthy noblemen of the court. They all lived happily ever after. Conclusion The first moral of the story is that beauty is a treasure, but graciousness is priceless. Without it, nothing is possible; with it, one can do anything. However, the second moral of the story mitigates the first one and reveals the criticism that without a doubt it is a great advantage to have intelligence, courage, good breeding, and common sense. These, and similar talents come only from heaven, and it is good to have them. However, even these may fail to bring you success, without the blessing of a godfather or a godmother.s
Fiction English Book
Keywords: English - Fiction Book